A judicialização de direitos trabalhistas é barreira à consciência de classe? um estudo sobre a exploração do trabalho como expressão da “questão social” - Matsumoto,Thaís Yumi (2021)
The Federal Constitution of 1988 imposes that the legal provision of social rights was not enough for their realization, since the Government, by adopting neoliberal practices, based on flexible accumulation, promoting destruction of the worker’s social protection, with special emphasis on the 2017 Labor Reform. In this context, there is an overvaluation of the Labor Court, a member of the Judiciary, generally requested by workers and also the state instrument that exercises the function of “pacifying” social conflicts, through judicial agreements. The main objective of the study was to understand if the judicialization of labor rights presents itself as a barrier to the class consciousness, focusing on the exploration of the workforce as an expression of the “social issue”. For this, we approached the social reality of workers who transformed their life stories at work into legal proceedings. This is a qualitative research, carried out through a critical dialectical approach, based on the analysis of the object of study, the category of work in bourgeois society, in its connection with the theoretical-methodological categories of totality, contradiction and historicity. A union leader of the professional category was presented, declared semi-structured with journalists – two of whom had different judicial representations, one by the Union and the other by a lawyer, and had a common request for overtime – and a union leader of the professional category, in addition to the bibliographic survey and documental research of the labor lawsuits of two research participants. It was found that the Labor Court stands out as a scenario, guaranteeing and violating the rights of the working class. Finally, it was possible to observe that this same space has also been providing conditions for the labor union to exercise its primordial role in the fight for classes and, thus, reiterating that the fight against the destruction of labor rights must be made collectively